Perioperative care of an adolescent with factor XI deficiency during posterior spinal fusion. - G. Parizek; B. Hall; R. Beltran; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal (PACCJ))
Factor XI (FXI) deficiency (Rosenthal disease or hemo- philia C) is a uncommon autosomal recessive bleeding disorder. Clinical signs and symptoms of factor XI de- ficiency are generally limited; however, significant bleeding may occur following trauma or a surgical pro- cedure. We present an adolescent with factor XI defi- ciency who presented for anesthetic care during posterior spinal fusion. The processes responsible for normal blood coagulation are presented, previous reports of peri- operative care of patients with factor XI deficiency re- viewed, and suggestions for perioperative care discussed.